2021
DOI: 10.1177/15589447211052759
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Distal and Proximal Approaches for Local Corticosteroid Injection in Carpal Tunnel Syndrome Management: A Randomized Controlled Trial

Abstract: Background: The present, open-labeled study aimed to compare the distal approach (DA) for local corticosteroid injection (LCI) with the conventional proximal approach (PA) in alleviating the symptom and improving the electrodiagnostic parameters of the patients with carpal tunnel syndrome (CTS). Methods: A total of 60 participants with nonsevere CTS were included in the present randomized controlled trial (RCT), of which 29 and 31 were assigned to the DA and PA groups, respectively. Each group received a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Pooled Analysis of BCTQ BCTQ was available in three studies [10,22,23], including 121 patients in the DA group and 124 patients in the PA group. The summarized estimate of effect size indicated that there was no significant difference in BCTQs (SMD 0.11; 95% CI -0.14 to 0.36; P = 0.39; Fig.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pooled Analysis of BCTQ BCTQ was available in three studies [10,22,23], including 121 patients in the DA group and 124 patients in the PA group. The summarized estimate of effect size indicated that there was no significant difference in BCTQs (SMD 0.11; 95% CI -0.14 to 0.36; P = 0.39; Fig.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Pooled Analysis of VAS VAS was described in three papers [22][23][24], with 65 patients in the DA group and 68 patients in the PA group. The pooled estimate of effect size showed that the VAS did not differ significantly between the two groups (MD -0.34; 95% CI -0.81 to 0.13; P = 0.15; Fig.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations